Audiological differences in healthy individuals with generalized joint hypermobility: a case-control study - Taş, Memduha; Tuna, Filiz; Yılmaz, Şüle (The European Research Journal, 2022)
Objectives: Despite the prevalence of generalized joint hypermobility (GJH), the audiological functions of individuals with GJH have not been documented. This study aimed to investigate audiological findings in individuals with GJH. Methods: This observational, cross-sectional, controlled study was conducted between May 2017 and August 2017. The mean age of all participants was 20.25 ± 0.75 years (range: 19-22 years). The generalized joint hypermobility consisted of individuals with a Beighton score of ≥ 5, while the controls with a Beighton score of ≤ 4. Pure-tone audiometry, immittance audiometry, and Transient Evoked Otoacoustic Emsission (TEOAE) testing were performed on subjects with generalized joint hypermobility (n = 25, mean age: 20.24 ± 0.72 years) and sex- and age-matched healthy controls (n = 31, mean age: 20.26 ± 0.77 years). Results: There were no significant differences in the mean hearing thresholds between the groups, although six (5.4%) ears in the GJH group had thresholds > 15 dB at one (five ears) or more frequencies. Significant differences were detected between the groups in the left ear for TEOAEs at 4 kHz and acoustic reflex thresholds. Conclusions: Individuals with GJH have some audiological differences that may be a predictor of changes related to future hearing loss. Further studies that involve larger samples and include participants of different ages are needed in order to determine whether individuals with GJH are more prone to hearing loss.